Cardiopulmonary Ultrasound Patterns of Transient Acute Respiratory Distress of the Newborn: A Retrospective Pilot Study - Maria Pierro; Roberto Chioma; Consuelo Benincasa; Giacomo Gagliardi; Lorenzo Amabili; Francesca Lelli; Giovanni De Luca; Enrico Storti (MDPI AG, 2023)
Acute transient respiratory distress in the first hours of life is usually defined as transient tachypnea of the newborn (TTN). TTN is a respiratory self-limiting disorder consequent to delayed lung fluid clearance at birth. While TTN is the most common etiology of respiratory distress near term, its pathogenesis and diagnostic criteria are not well-defined. Lung ultrasound and targeted neonatal echocardiography are increasingly being used to assess critically ill infants, although their combined use to improve diagnostic precision in neonatal intensive care units has not yet been described. This retrospective pilot analysis aimed to identify possible cardiopulmonary ultrasound (CPUS) patterns in term and late preterm infants suffering from transient respiratory distress and requiring non-invasive respiratory support. After retrospectively revising CPUS images, we found seven potential sonographic phenotypes of acute neonatal respiratory distress. Up to 50% of the patients presented with signs of increased pulmonary vascular resistance, suggesting that those patients may be diagnosed with mild forms of persistent pulmonary hypertension of the newborn. Approximately 80% of the infants with a history of meconium-stained amniotic fluid displayed irregular atelectasis, indicating that they may have suffered from mild meconium aspiration syndrome. CPUS evaluation may improve accuracy in the approach to the infants presenting with transient acute respiratory distress, supporting communication with the parents and carrying important epidemiological consequences.